Lodo em lagoas de polimento: acúmulo e implicações no comportamento hidrodinâmico e no desempenho do sistema - Thiago Emanuel Possmoser Figueiredo Nascimento (2014)
Polishing ponds are a technology with great potential for application in developing countries because they are units that combine aerobic treatment to an efficient anaerobic treatment (UASB). This combination enables the reduction in area compared to the facultative ponds and control of airborne odors when compared to systems that employ anaerobic lagoons, while maintaining efficiency and certain simplicity of systems. On the other hand sludge accumulation is inherent in this systems. This accumulation of sludge reduces the volume in the ponds, generally in irregular forms, causing changes in hydrodynamics and possible implications on system performance. Thus, the aim of this study was to evaluate the accumulation of sludge an its influence on the hydrodynamics and treatment performance of system composed of polishing ponds, after 11 years of operation. Sludge volume was evaluated by using a bathymetry rod for three polishing ponds in series (P1, P2 and P3) beyond a simplified mass balance for the difference of suspended solids between influent and effluent was also used to compare with the mass of solids observed in sediment of pond (1st phase). The second phase was to assess the hydrodynamics and performance of two ponds in parallel, one with 40% of its volume filled with sludge, called Pwith-sludge and other pond without sludge, called Pwithout-sludge. The implication of sludge in hydrodynamics was evaluated through tracer tests with sodium chloride in the field and software simulations (using Computational Fluid Dynamic software - CFD), performed in a pond with sludge (Pwith-sludge) and without sludge (Pwithout-sludge). The system performance was evaluated over 7 months for key performance parameters (BOD, COD, TSS, E. coli). In phase 1 it was observed that after 11 years of operation, 92% of the accumulated mass was in P1 and that occupied 40% of the total volume of the pond. The other 8% of the mass, found himself accumulated in P2 and this filled 8% of the total volume of this unit. Through the simplified mass balance it was possible to estimate a large production of suspended solids in the system (algal biomass). In the 2nd phase, the practice of tracer tests identified a greater dispersion number for Pwith-sludge (d=0.72) than for Pwithout-sludge (d=0.31), indicating that the presence of sludge contributes to the increase of the dispersion number of the system and that both systems were similar to a completely-mixed reactor. The actual TDH was greater than the theoretical TDH. Through simulations and results with tracer test in the field was possible to make assumptions that this was due to the type of output structure, thermal stratification and density tracer that made it difficult to recover the tracer used. The accumulation of sludge in the system observed was inferior to that found in anaerobic and facultative pond systems. Although the study shows that sludge affects hydrodynamics in the ponds, statistical evidence was not found that shows that the sludge influences the performance in pollutant removal in the system.